If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(6 + v) = 14 + -7v (6 * -3 + v * -3) = 14 + -7v (-18 + -3v) = 14 + -7v Solving -18 + -3v = 14 + -7v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '7v' to each side of the equation. -18 + -3v + 7v = 14 + -7v + 7v Combine like terms: -3v + 7v = 4v -18 + 4v = 14 + -7v + 7v Combine like terms: -7v + 7v = 0 -18 + 4v = 14 + 0 -18 + 4v = 14 Add '18' to each side of the equation. -18 + 18 + 4v = 14 + 18 Combine like terms: -18 + 18 = 0 0 + 4v = 14 + 18 4v = 14 + 18 Combine like terms: 14 + 18 = 32 4v = 32 Divide each side by '4'. v = 8 Simplifying v = 8
| y=-2x-21 | | 16t^2+10t-12=0 | | x-6/3=-10 | | -12x-3=2.67x+0 | | 6(3x-1)=8(1+2x) | | 12x+3=3x+0 | | -2+5p=-(1-4p)-5 | | -(x-8)=1-4(x+2) | | 2h+3/4=1/4(h+15) | | w-(-43)w=8 | | 4-x=7.3 | | -4(8r-4)+5r=-15+4r | | 12x+3=2.67x+0 | | 35-7n=-7(7+4n) | | 3m^2+11m+15=0 | | 4y-6+y=14+5y-4y | | 3x^2-5=20 | | 0.2(15k-1.5)=0.5(7.5-3k) | | -2.25x=-11-4 | | -6(m-6)=37-5m | | 4(x-7)(x-9)(x+4)=0 | | 4(3x+4)=14 | | 9/4t=-11-4 | | 10x+20y=13000 | | x=7006-4159 | | 2x^2+11x-5=0 | | 8[x-(5x-8)]=6-9x | | x(2)=(x+1)(x+1) | | -29=5v-9 | | 6(5a+6)=6(a-6) | | 2x^2+5x+2=5 | | 5[x-(6x-5)]=1-8x |